Assessment of the potential for maladaptive parenting in expectant fathers with the Adult-Adolescent Parenting Inventory (AAPI) - Tiller, C M (Journal of child and adolescent psychiatric and mental health nursing, 1991)
The purpose of this investigation was to determine if expectant fathers could be assessed for potential maladaptive parenting with the Adult-Adolescent Parenting Inventory (AAPI). Image factor analysis with matrix rotation by SPSSx was used to replicate Bavolek's (1984) earlier work. It was concluded that the AAPI was appropriate for use with expectant fathers because their responses were not significantly different than those of other populations. The 232 subjects' scores indicated that although they had appropriate attitudes toward empathy and family roles, they had limited knowledge of child growth and development and had strong beliefs in physical discipline. Recommendations include the need for further studies using the AAPI to validate its effectiveness as a predictive tool in the primary prevention of child abuse and neglect.